PERAN PEMERINTAH SEBAGAI REGULATOR DAN PENYEDIA LAYANAN DALAM PENGELOLAAN SAMPAH DI KELURAHAN DELIMA KECAMATAN TAMPAN KOTA PEKANBARU - Septian Julifar; Sukendi Sukendi; Yusni Ikhwan Siregar (Jurnal Ilmu Lingkungan, 2020)
A study on the role of the government as a regulator and service provider on domestic waste April 2020 in. The survey were done in Delima Village, Tampan Sub-District of Pekanbaru City. Community on the stakeholder were sampled purposively for twenty people, and interviewed according to criteria (1) living in Delima Village, (2) family living around the piles up of domestic garbage, and (3) person involving in local waste management. The result appeared that the government has not regulated significantly (t < 0.05). While the government role as a service provider in domestic waste management were significantly done. Multiple linear regresion analysis on those government role showed significantly which regulator role (0,001<0.05) and for service provider (4,237 < 2,109. It is concluded that the government has fairly role as a regulator and as a service provider on domestic waste management in Tampan Subdistrict Pekanbaru City.